Green health an A-to-Z guide - Ogunseitan, Oladele; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2011)
Exploring topics ranging from organic food and health to hazardous waste, 150 articles provide an outstanding reference source examining the green movement within the contexts of personal health and the healthcare industry.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Health attitudes; Health behavior; Green movement; Electronic books